Environmentally Specific Transformational Leadership and Employee’s Pro-environmental Behavior: The Mediating Roles of Environmental Passion and Autonomous Motivation - Li, Zongbo; Xue, Jiaxin; Li, Rui; Chen, Hong; Wang, Tingting (Frontiers in Psychology, 2020)
Organizational management practices in promoting sustainable development of ecological environment are becoming a crucial way for enterprises to gain competitive advantages. However, whether the goal of such practices can be achieved depends on employees’ perception of environmental problems and the way they act. Therefore, it is important to stimulate employees’ pro-environment behaviors through management activities. Building on affective events theory and self-determination theory, we examined the effect of environmentally-specific transformational leadership on employees’ pro-environmental behaviors (PEBs), as well as the potential mediating effects of environmental passion and autonomous motivation. A cross-sectional survey was conducted among 214 employees in China. Structural equation modeling was performed to test the theory-driven models. The results showed that environmentally-specific transformational leadership positively influenced employees’ PEBs, and that environmental passion and autonomous motivation mediated this influence respectively. Furthermore, multiple-mediating testing results showed that environmental passion and autonomous motivation played sequential mediating roles in the link of environmentally-specific transformational leadership to PEBs. This research unveiled environmental passion and autonomous motivation as underlying mechanisms that accounted for the link between transformational leadership and PEBs.